Türkiye’s Penal Reform on Domestic Violence: From the Opuz Case to the 2020s - Derya Tekin (Ceza Hukuku ve Kriminoloji Dergisi)
Among the Organisation for Economic Co-operation and Development countries, Türkiye has the highest prevalence of violence against women (VAW). Turkish legislators have had to keep developing their penal regulations regarding VAW and domestic violence in particular. The study has adopted feminist legal theory as its theoretical perspective and aims first to reveal the nature and extent of the phenomenon of domestic violence in Türkiye in light of the cases Opuz v. Türkiye (2009) and Huseyin Pasali and Others v. Türkiye (2020) that were brought before the European Court of Human Rights. These two symbolic domestic violence cases in Turkish history have triggered a penal reform regarding the issue. Despite Türkiye announcing its withdrawal from the Istanbul Convention in 2021, the international covenants Türkiye has ratified provide significant guidance for Turkish legislators. With the most recent additions to the Turkish Criminal Code in the 2020s, penal regulations have attained a relatively more gender-sensitive character. With the 2021 and 2022 amendments, divorced women and women in general have been well recognized as particular victim groups in the Turkish context. Intentional killing, intentional injury, torment, and deprivation of liberty committed against a divorced spouse have been regulated as aggravating circumstances of the crimes in question. Moreover, prosecuting these crimes does not require a complaint in the current law. Alongside this, the criminalization of stalking and prohibition of mediation in relation to stalking are also significant developments. Intentional aggravated murder of a woman now qualifies this crime to require life imprisonment. New provisions also increase the lower terms of the punishment in relation to the crimes of injury, torture, torment, and threats when committed against a woman. All these reforms seem to ignore some gender dimensions of the problem, namely the gender of the offenders and the motives behind the crimes. However, these are still significant in terms of acknowledging the vulnerable and subordinate status of female victims in Türkiye in relation to such crimes. In light of the costs the Turkish State has paid historically, these relatively gender-sensitive penal regulations are promising for Türkiye’s struggle with VAW. Now, the future can be built on the argument that VAW is a gender-based problem that involves not only female subordination or vulnerability but also male supremacy, which Turkish legislators should consider more when enacting penal provisions.